(untitled) - Rosebrock, Eric (San Francisco, 2004)
This is the book for webmasters, developers, and IT departments looking to create sophisticated Internet applications with open-source technologies. Setting Up Lamp teaches you how to develop a complete web server solution from the ground up. You'll learn how to install, configure, use, and integrate all four LAMP components--Linux operating system, Apache web server, MySQL database manager, and PHP programming language. And, you'll discover how to get support from open-source web sites and communities. Focusing on fundamental concepts of the technologies, this book is not version specific. In fact, it addresses how to use future updates of LAMP technologies to extend its shelf life.
Keywords: Ngôn ngữ lập trình máy tính,Web sites,PHP (Computer program language),Website; Design,Thiết kế